Bracketology in Pharmacy Education: The Impact of March Medication Madness on Student Engagement and Knowledge - Allison Hursman; Natasha Petry; Rebecca Brynjulson; Jeanne Frenzel; Donald Miller; Elizabeth Monson; Megan Orr; Lisa Richter; Joan Viets Nice (University of Minnesota Libraries Publishing, 2024)
Introduction. Gamification is being used in pharmacy education as a learning strategy to engage learners with educational content in innovative ways.  Bracketology is one type of gamification that has not been described in pharmacy education literature.  The goal of implementing a March Medication Madness activity was to increase student engagement and knowledge.  The associated study aimed to assess activity goal achievement. Innovation.  The March Medication Madness project was developed for use in a capstone course offered in the final semester of the didactic pharmacy curriculum.  Students created medication related pearls which were paired together in a 32-team tournament style bracket.  Students then completed brackets to predict the winning pearls and voted biweekly to determine the most clinically significant pearl.  Student knowledge was assessed pre- and post-activity along with a post-activity perception assessment. Critical Analysis.   Most students either agreed or strongly agreed that the activity increased understanding and stimulated interest in course material, while adding an element of fun to the course. There was a statistically significant increase (t51=3.34, p=0.002) in the average percentage of multiple-choice questions students answered correctly from the pre-test (57.7%±1.5%) to the post-test (63.1%±1.9%).  Pearls that progressed the farthest within the voting were no more likely to be associated with an increase in knowledge than pearls that were eliminated in the first two rounds. Next Steps.  Implementation of a bracketology activity was perceived as fun and engaging for students, and they felt that it aided in their understanding of course material.  However, the actual increase in knowledge was limited. This shows the importance of structuring gamification in a way that truly provides educational value and enforces the need to make modifications to the activity for future iterations to promote student learning.